Analysis of factors affecting the selection of residence and housing in Tabriz city - Mina Farokhi someh; Shahrivar Rostaei; Rasoul Ghorbani (تحقیقات کاربردی علوم جغرافیایی)
Today, given the rapid growth of the world's population and its focus on cities, access to quality housing by urban dwellers is an essential component of influencing the long-term outlook of human communities. At the same time, considering the widespread impacts of housing on urban environments and on the economic, social and physical life of the city and its citizens, it is important to identify the factors that influence the choice of place of residence and housing. The residence has been emphasized on housing features. The type of research was applied and descriptive-analytical in nature; the method of data collection is library and field (questionnaire). The study population consisted of 384 households living in Tabriz metropolitan area. Then, tests (descriptive and inferential statistics) will be used and finally by diagnostic analysis using SPSS 22 and GIS software will analyze the relationships between variables. The results showed that demographic and lifestyle indices affect residence and housing choice and when demographic characteristics are combined with lifestyle, the choice of residence by the households is examined based on differences. Individual and lifestyle are important. Also, based on the results of the research, selection of residence and housing has a significant relationship with access to business centers, childcare centers, cultural centers, pedestrian access, parking and home warning cameras.